2016
DOI: 10.3171/2015.8.spine141097
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of degenerated ovine lumbar discs by STRO-3–positive allogeneic mesenchymal precursor cells combined with pentosan polysulfate

Abstract: OBJECTIVE Disc degeneration and associated low-back pain are major causes of suffering and disability. The authors examined the potential of mesenchymal precursor cells (MPCs), when formulated with pentosan polysulfate (PPS), to ameliorate disc degeneration in an ovine model. METHODS Twenty-four sheep had annular incisions made at L2–3, L3–4, and L4–5 to induce degeneration. Twelve weeks after injury, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 73 publications
(89 reference statements)
2
24
0
Order By: Relevance
“…As described above injection of enzymes leads to proteoglycan loss, an essential component of the pathophysiological process of disc degeneration observed clinically. A criticism of the chondroitinase ABC for inducing disc degeneration is that the viability of native disc cells is largely preserved, enabling regeneration of the extracellular matrix [ 99 ].…”
Section: Intervertebral Disc Degenerationmentioning
confidence: 99%
“…As described above injection of enzymes leads to proteoglycan loss, an essential component of the pathophysiological process of disc degeneration observed clinically. A criticism of the chondroitinase ABC for inducing disc degeneration is that the viability of native disc cells is largely preserved, enabling regeneration of the extracellular matrix [ 99 ].…”
Section: Intervertebral Disc Degenerationmentioning
confidence: 99%
“…While larger studies fulfilling these requirements are currently under way in various laboratories and results are eagerly awaited, it was previously already shown that MSCs are able to promote disc regeneration in dogs with experimentally induced IVD degeneration . Importantly, similar results were observed in sheep, not only after nucleotomy, but also after annular injury and annular incision, highlighting the therapeutic potential of MSCs in large animal models and hence possibly also in humans.…”
Section: Yesmentioning
confidence: 80%
“…11,17 Therefore, the ovine spine has been used as a model for intervertebral disc degeneration and test implant devices and in the preclinical investigation of cellular therapies. 7,11,[18][19][20] Analyses of sheep cervical spine biomechanics and radiological anatomy parameters confirmed a high similarity to measures in human cervical spines, which allow the use of similar sized implants and instruments as under clinical conditions in humans. 11,17 Compared with human cervical spine, the sheep disc is even higher in superior-inferior measures, which, according to the largely avascular nature of the intervertebral disc and dependence on diffusion to meet nutritional requirements, seems favourable for an ambitious disc regeneration model.…”
Section: Discussionmentioning
confidence: 94%
“…Ovine disc models have previously been described to analyse degeneration processes and preclinical regeneration therapies. 5,20 Most of these models use the sheep lumbar spine. Beside the fact that sheep are one of the most ideal disc models stated by Daly and colleagues until now, there is only limited data for disc degeneration and regeneration models in the ovine cervical spine.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation